THE IMPORTANCE OF PLANT CONSERVATION AND ITS ROLE IN BOTANY (Modern education and development, 2025)
Nature is one of the most important factors for the life and future of humanity, and plants are an integral part of it. Plants produce oxygen, protect the soil from erosion, ensure ecological balance, and are a source of food, medicine, and raw materials for humans and animals. Therefore, protecting the plant world is not only of ecological, but also of economic and scientific importance.This article provides information on the concept of flora, the definition of flora by legal scholars, statistics on plant species in the world and in the Republic of Uzbekistan, flora objects, the experience of some developed countries in protecting flora, the types of flora objects established in the legislation of the Republic of Uzbekistan and the foundations of their protection.